Seeing beyond the smoke: smallholder farming in Papua New Guinea in a changing world - Hazenbosch, M (2021)
Smallholder farming plays a crucial role in sustaining the food security and livelihoods of billions of people. Rapid social-ecological changes, including population growth, climate change and the incursion of external actors, are affecting smallholder farmers. In this thesis, I evaluate the changing social-ecological system of smallholder farming, and how interventions can support farmers to respond, using a case study in Papua New Guinea (PNG).